A chromosome‐level genome assembly reveals the genetic basis of cold tolerance in a notorious rice insect pest, Chilo suppressalis. (6th November 2019) - Ma, Weihua; Zhao, Xianxin; Yin, Chuanlin; Jiang, Fan; Du, Xiaoyong; Chen, Taiyu; Zhang, Qinghua; Qiu, Lin; Xu, Hongxing; Joe Hull, J.; Li, Guoliang; Sung, Wing‐Kin; et al.
Abstract: The rice stem borer, Chilo suppressalis, is one of the most damaging insect pests to rice production worldwide. Although C. suppressalis has been the focus of numerous studies examining cold tolerance and diapause, plant–insect interactions, pesticide targets and resistance, and the development of RNAi‐mediated pest management, the absence of a high‐quality genome has limited deeper insights. To address this limitation, we generated a draft C. suppressalis genome constructed from both Illumina and PacBio sequences. The assembled genome size was 824.35 Mb with a contig N50 of 307 kb and a scaffold N50 of 1.75 Mb. Hi‐C scaffolding assigned 99.2% of the bases to one of 29 chromosomes. Based on universal single‐copy orthologues (BUSCO), the draft genome assembly was estimated to be 97% complete and is predicted to encompass 15, 653 protein‐coding genes. Cold tolerance is an extreme survival strategy found in animals. However, little is known regarding the genetic basis of the winter ecology of C. suppressalis . Here, we focused our orthologous analysis on those gene families associated with animal cold tolerance. Our finding provided the first genomic evidence revealing specific cold‐tolerant strategies in C. suppressalis, including those involved in glucose‐originated glycerol biosynthesis, triacylglycerol‐originated glycerol biosynthesis, fatty acid synthesis and trehalose transport‐intermediate cold tolerance. The high‐quality C. suppressalis genome provides a valuable resource for research into a broad range of areas in molecular ecology, and subsequently benefits developing modern pest control strategies.